2022
DOI: 10.1108/mf-10-2021-0519
|View full text |Cite
|
Sign up to set email alerts
|

Access to finance, social capital and the improvement of corporate performance: evidence from Southeast Asia

Abstract: PurposeThis study examines the influence of access to finance and social capital on the improvement of the corporate performance of non-listed firms of Southeast Asian countries. Furthermore, this paper also explores the mediating role of firms' access to finance between the association of social capital and the improvement of corporate performance.Design/methodology/approachThis study utilizes the Bank Business Environment and Enterprise Performance Survey from 2015 to 2017. Specifically, the survey was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 127 publications
1
14
0
Order By: Relevance
“…The data of 427 participants were analyzed using statistical package for social sciences (SPSS) and PLS-SEM software to generate the study's findings. The present study selects PLS-SEM over covariance-based SEM as the primary data analysis software because it is more suitable for the prediction-oriented approach (Kijkasiwat et al. , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of 427 participants were analyzed using statistical package for social sciences (SPSS) and PLS-SEM software to generate the study's findings. The present study selects PLS-SEM over covariance-based SEM as the primary data analysis software because it is more suitable for the prediction-oriented approach (Kijkasiwat et al. , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The attributes of the data collected are self-reported so CMB may threaten the validity of the results (Kijkasiwat et al. , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, combine resource based view (Barney & Barney, 2001) and dynamic capabilities theory (Teece et al, 2009;Teece et al, 2016), in framing the present study, it will enhance to our understanding of how organizations become more agile by optimizing the strategic role of leadership. Second, there are still many research opportunities that can be done with leadership and organizational agility which raises several new variables that are not directly related, such as fintech (Pizzi, Corbo, & Caputo, 2021), strategic planning (Iborra, Safón, & Dolz, 2020), learning, new product development (Lin & Chen, 2021;Stock, Tsai, Jiang, & Klein, 2021), corporate foresight, environment uncertainty (Ahmed, Umrani, Yousaf, Siddiqui, & Pahi, 2021;Koval et al, 2021), balance scorecard, digitalization, industri 4.0 dan performance (K & Ranjit, 2022;Kijkasiwat, Shahid, Hassan, & Hunjra, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This has been evidenced by Ju et al [2] which also shows that financial resources, customer resources, and human resources obtained from personal networks (family, community, and government) contribute to firm performance in China. Kijkasiwat et al [34] have shown that financial resources accessed through social capital have a positive impact on the operational performance of non-listed firms in Southeast Asian countries. Tourism businesses have been severely affected by the COVID-19 pandemic.…”
Section: The Mediating Role Of Re Resource Acquisition Between Social...mentioning
confidence: 99%